Evaluation of the effect of microclimate differences on activity of codling moth, Cydia pomonella (Lepidoptera : Tortricidae), using pheromone trap capture data collected in apple and pear orchards in the Langkloof Region - Moehrke, Axel H. (Stellenbosch : Stellenbosch University, 2012)
Study project (M.Sc.Agric.) -- University of Stellenbosch, 1999.